Revitalisasi Dinding Melalui Pembuatan Mural dengan Narasi Sejarah Jamblang, Cirebon: Wall Revitalization Through Making Murals with Jamblang History Narrative, Cirebon - Miky Endro Santoso; Elliati Djakaria; Tessa Eka Darmayanti; Krismanto Kusbiantoro; Cindrawaty Lesmana; Irfan Nurrachman; Ferlina Sugata; Leonardo Leonardo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Jamblang Chinatown, Cirebon was once known as a trading city during the Dutch colonial period, as a place for buying and selling and stopping by traders from various regions through the river that flows nearby. The river is a means of transportation that brings ships from the interior of Cirebon to the Java Sea, and vice versa. However, the current situation is reversed because Jamblang is like a "dead city" that is almost forgotten. The government and the community have a dream to revive the Jamblang Chinatown area. Through this PKM activity, a team of lecturers and students of the Faculty of Fine Arts and Design at Maranatha Christian University seeks to revive Jamblang Chinatown by making murals with the surrounding community, as well as providing education as well as performances for the surrounding community through PKM activities. The attraction of making murals containing the historical value of Jamblang. The approach taken is a participatory collaborative workshop with local residents, through mentoring and education. The result achieved is a mural with the theme Mural History Jamblang, which is located on a 90-degree wall and is located in front of Vihara Dharma Rhakita, Jamblang, Cirebon Regency. They participate in the process of making murals. Other residents are interested in knowing the meaning contained in the visualization of the mural. And many are just selfies with a mural as a background. This mural-making attraction is also quite successful as one of the activities that attract public attention during the 2022 Jamblang Festival.